Topologically frustrated ionisation in a water-ammonia ice mixture. Issue 1 (December 2017) - Liu, C.; Mafety, A.; Queyroux, J.; Wilson, C. W.; Zhang, H.; Béneut, K.; Le Marchand, G.; Baptiste, B.; Dumas, P.; Garbarino, G.; Finocchi, F.; Loveday, J.; et al.
Abstract Water and ammonia are considered major components of the interiors of the giant icy planets and their satellites, which has motivated their exploration under high P–T conditions. Exotic forms of these pure ices have been revealed at extreme ( megabar) pressures, notably symmetric, ionic, and superionic phases. Here we report on an extensive experimental and computational study of the high-pressure properties of the ammonia monohydrate compound forming from an equimolar mixture of water and ammonia. Our experiments demonstrate that relatively mild pressure conditions (7.4 GPa at 300 K) are sufficient to transform ammonia monohydrate from a prototypical hydrogen-bonded crystal into a form where the standard molecular forms of water and ammonia coexist with their ionic counterparts, hydroxide (OH− ) and ammonium ( NH_4^ + ) NH 4 + ions. Using ab initio atomistic simulations, we explain this surprising coexistence of neutral/charged species as resulting from a topological frustration between local homonuclear and long-ranged heteronuclear ionisation mechanisms. Water and ammonia are major constituents of icy planet interiors, however their phase behaviour under extreme conditions remain relatively unknown. Here, the authors show that ammonia monohydrate transforms under pressure into an alloy composed of molecules as well as ions, owing to a topological frustration.